Pengaruh Proporsi Dewan Komisaris Independen dan Komite Audit terhadap Kinerja Keuangan Perusahaan (Studi terhadap Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2017-2021) - Riahman Damanik, Erdy; Purnamasari, Atika (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To determine the effect of the proportion of independent commissioners and audit committees on the financial performance of food and beverage companies listed on the IDX in 2017-2021. Background Problems: The growth of the industrial sector experienced the sharpest growth in this sectoral index, triggered by the increase in the consumptive behavior of the Indonesian people. Novelty: For IDX30 indexed companies for the 2018-2019 period, the board of directors and committee boards have influence over ROE and independent commissioners have no influence over ROE. Research Methods: The sampling technique used was purposive sampling using 17 companies and using the SPSS analysis tool. Finding/Results: The sampling technique used was purposive sampling using 17 companies and using the SPSS analysis tool. Conclusion: Companies are advised to monitor and control the use of debt because it will affect profitability.